2004
DOI: 10.1097/01.brs.0000137287.67388.0b
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Transpedicular Screw Fixation in the Subaxial Cervical Spine

Abstract: The major finding of the current study was the higher stability of pedicle screws over lateral mass fixation with respect to primary stability and stability after cyclic loading. From a biomechanical point of view the use of pedicle screws in the subaxial cervical spine seems justified in patients with poor bone quality and need for multisegmental fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 20 publications
2
136
0
10
Order By: Relevance
“…Hence, fatigue analyses are indicated that might show distinct differences among the constructs tested here [19,41]. Kothe [34] performed segmental stabilization of 3-level circumferentially destabilized spines with segmental fixation C3-C6 using all-LMS or all-CPS constructs. Significant differences in primary stability existed only for lateral bending.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, fatigue analyses are indicated that might show distinct differences among the constructs tested here [19,41]. Kothe [34] performed segmental stabilization of 3-level circumferentially destabilized spines with segmental fixation C3-C6 using all-LMS or all-CPS constructs. Significant differences in primary stability existed only for lateral bending.…”
Section: Discussionmentioning
confidence: 99%
“…We constructed a 2-level corpectomy model with removal of the PLL, others did not [16, 34,49], while the PLL is a known main segmental stabilizer [15]. Ianuzi [23] analyzed the stability afforded by an anterior constrained plate, posterior-constrained LMS, and 360°construct for a 1-level corpectomy model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomechanical studies [24,53,54,61,75,86,95,99,100,102,104] and previous clinical studies [11, 22, 48, 55, 61, 62, 66, 73, 75, 90, 95, 100-102, 104, 118] called into question the use of anterior devices in multilevel fusions and corpectomy cases, and support the addition of posterior stabilization, particularly that of pedicle screw fixation [58,59,61,97,100]. However, one has to consider that with the biomechanical advantage of supplemental posterior stabilization is the addition of a second significant surgery and added risks, particularly in elderly and frail patients.…”
Section: Clinical Failures In Multilevel Anterior Cervical Constructsmentioning
confidence: 99%